Traffics and wildlife: A preliminary study on road-kill - Rustiati, Elly Lestari (Universitas Jambi, 2009)
This paper presents the preliminary finding on road kill survey by direct observations onthe high ways. The road-kills recorded of small wildlife, including medium size-mammal (2.50%, n =1), birds (5.00%, n = 2) and small mammals (92.50%, n = 37). The small mammals include the mostcommon mammals in the areas, squirrels, raccoons, skunks and woodchuck. Of mammals, squirrels(35.00%) were the highest recorded, followed by woodchucks (25.00%), mice/shrew (17.50%),raccoons (10.00%), skunk (5.00%) and domestic cat (2.50%) respectively. It seems road-kill wascaused by conflict between the wildlife natural habitat as well as its ecological behavior and roaddevelopment.